Self-efficacy for prevention of diabetic foot ulcer among patients with type 2 diabetes mellitus - Janu Purwono; Ludiana Ludiana; Rita Sari (Malahayati International Journal of Nursing and Health Science, 2021)
Background: It is estimated that by 2040 there will be more than 642 million people with diabetes in the world and 80% of those people will live in developing countries. This means that every 6 seconds there is one person with diabetes who dies. WHO estimates that the number of DM sufferers in Indonesia will increase from 8.4 million in 2000 to around 21.3 million in 2030. Currently, Indonesia is ranked as the fourth largest DM sufferer after China, India, and the US. The prevalence of diabetes mellitus in Lampung Province has increased with prevalence (1.2%). Purpose: To determine of self-efficacy for prevention of diabetic foot ulcers among patients with type  2 diabetes mellitusMethod: A descriptive correlational design to determine the relationship between variables. The sample is 107 respondents and the sample is taken using purposive sampling. Data were collected using a questionnaire, foot care confidence scale (FCCS), and treatment behavior scale for diabetes (FCBS for Diabetes). The independent variable of this research is self-efficacy of DM patients and the dependent variable of this research is foot care activity. Data analysis using Spearman Rho correlation test (α = 0.05).Results: Spearman Rho correlation test showed that there was a relationship between self-efficacy of people with diabetes mellitus and behavior in foot care activities. p-value = 0.000 (p <0.05), r = 0.786.Conclusion: High self-efficacy in respondents with type-2 diabetes mellitus will increase behavior related to foot care activities.